2020
DOI: 10.1177/1557988320945465
|View full text |Cite
|
Sign up to set email alerts
|

African Immigrant Health: Prostate Cancer Attitudes, Perceptions, and Barriers

Abstract: Prostate cancer (PCa) is the second leading cause of cancer-related death among Black men who present with higher incidence, mortality, and survival compared to other racial groups. African immigrant men, however, are underrepresented in PCa research and thus this research sought to address that gap. This study applied a social determinants of health framework to understand the knowledge, perceptions, and behavioral tendencies regarding PCa in African immigrants. African immigrant men and women residing in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…These findings shed light on the challenges faced by AI individuals, particularly in terms of stress, financial strain, and discrimination – all of which negatively impact one's health( Hassan et al., 2021 ; Nkimbeng et al., 2021 ; O'Connor et al., 2021 ). In our sample, 79-percent reported experiencing discrimination, which is consistent with recent literature indicating that the intersectional identity of being both Black and an immigrant exacerbates their discrimination experiences ( Malika et al., 2020 ; Nkimbeng et al., 2021 ). This is critical as studies suggest that AI experiencing discrimination tend to have poorer physical and mental health ( Nkimbeng et al., 2021 ; Szaflarski & Bauldry, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings shed light on the challenges faced by AI individuals, particularly in terms of stress, financial strain, and discrimination – all of which negatively impact one's health( Hassan et al., 2021 ; Nkimbeng et al., 2021 ; O'Connor et al., 2021 ). In our sample, 79-percent reported experiencing discrimination, which is consistent with recent literature indicating that the intersectional identity of being both Black and an immigrant exacerbates their discrimination experiences ( Malika et al., 2020 ; Nkimbeng et al., 2021 ). This is critical as studies suggest that AI experiencing discrimination tend to have poorer physical and mental health ( Nkimbeng et al., 2021 ; Szaflarski & Bauldry, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…A large proportion of the AI reported having insurance, visiting a doctor for routine visits regularly, using CAM and expressing distrust in the health system. While an overwhelming majority of the AI in this study had health insurance and had a medical visit at least once a year, several studies ( Malika et al., 2020 ; Omenka et al., 2020 ) have revealed that AI delay office visits until the illness is irrecoverable or severe enough to halt daily functioning. One of the reasons for this has been lack of discussion of CAM integration into health.…”
Section: Discussionmentioning
confidence: 89%
“…Validation of PRO measures is important in demonstrating PRO suitability and may assist in increasing healthcare providers' acceptance of PRO data. Racial differences in completion rates and preferences for the way patients report PROs [38,39] may exist as well. These complexities with PRO data interpretation highlight the need for adaptive approaches, such as adaptive trial designs that minimize the number of patients receiving subtherapeutic doses, and PRO tools that can be tailored accordingly as knowledge on treatment toxicities develops.…”
Section: Discussionmentioning
confidence: 99%